Fortaleza em perspectiva historica: poder publico e iniciativa privada na apropriação e produção material da cidade 1810-1933 - Andrade, Margarida Julia Farias de Salles (2012)
This thesis investigates urban transformations that took place in the city of Fortaleza (Brazil) between 1810 and 1933, examining governmental action and the role of the private sector in relation to land ownership and physical building of that city, focusing on its interurban space, its organization and actors involved. Given the history of urbanization, understood as a social process in its different scales - local, regional, national and international – this study sought to deal, in a long-term historical perspective, with this process continuities and ruptures. This thesis aims at contributing to develop new possibilities of its interpreting town planning history based on urban maps produced from primary sources of various kinds – city blue prints, urban development plans, legislation, census, and urban taxes archives - in order to interpret Fortaleza’s urban dynamic at different times. The central hypothesis is that, until 1933, Fortaleza’s growth was induced by urban regulatory plans produced by the public government, but the city was built by the private sector. It identifies the main roles of those involved in the private sector linked to the physical production of the city, giving them a face, setting individual and group profiles, and, above all, quantifying and spatializing their properties within the city fabric. It can, also, be noticed that largest urban estate landowners were businesspeople (from Ceará, Portuguese, and other foreigners) involved with international trade.